Plant Cell Expansion Methods and Protocols - Estevez, José M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume covers broad aspects of cell expansion in three different cell types: root hairs, pollen tubes, and hypocothyl cells. Chapters focus on the cutting-edge methods to study in detail several complex aspects of cell expansion such as secretion, endocytosis and recycling, cellular signaling and trafficking, and protein and polysaccharides cell wall biosynthesis in real time during cell expansion. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Plant Cell Expansion: Methods and Protocols is an essential reference book for plant scientist, molecular, and cell biologist as well as plant biochemists .
Penium margaritaceum as a Model Organism For Cell Wall Analysis Of Expanding Plant Cells -- Using Chemical Genomics to Study Cell Wall Formation and Cell Growth in Arabidopsis thaliana and Penium margaritaceum -- Optimized Method For Growing In Vitro arabidopsis Thaliana Pollen Tubes -- Imaging of Calcium Dynamics in Pollen Tube Cytoplasm -- Live Imaging of Root Hairs -- Improved ROS Measurement In Root Hair Cells -- A Root Hair Assay to Expedite Cell Death Research -- Vacuolar Staining Methods in Plant Cells -- Live Cell Imaging Of FM4-64, A Tool For Tracing The Endocytic Pathways In Arabidopsis Root Cells -- Salt-Stress Regulation Of Root System Growth And Architecture In Arabidopsis Seedlings -- Quantification Of Fluorescent Reporters in Plant Cells -- Live Cell Imaging Of The Cytoskeleton And Cell Wall Enzymes In Plant Cells -- Using the Split-Ubiquitin Yeast Two-Hybrid System to Test Protein-Protein Interactions of Transmembrane Proteins -- Activation Tag Screening For Cell Expansion Genes in Arabidopsis thaliana -- Bifc For Protein-Protein Interactions and Protein Topology: Discussing An Integrative Approach For An Old Technique -- N-Glycosylation and Plant Cell Growth -- Peptide Separation Methodologies for In-depth Proteomics -- Structural And Mechanical Characterization Of Growing Arabidopsis< Plant Cell Walls.
Keywords: Plant science; Botany; Plant physiology; Plant Sciences; Plant Physiology